Performance Analysis of ABM Distributed Simulation for Real Crowd Evacuation Scenarios - Alghazzawi, Mohammed J. (2017)
Managing crowds is a key problem in a world with a growing population. Being able to predict and manage possible disasters directly affects the safety of crowd events. This kind of problem can be modeled using Agent-Based Model techniques and consequently simulated in order to study evacuation strategies. Our aim from this paper is to prove that this model albeit simple can be expanded and adapted for experts to test various scenarios and validate the outcome of their design. Preliminary experiments are carried out using different initial locations for the agents inside Fira of Barcelona building, whose results are presented, validated and discussed. We shown that crowd evacuation problem has bottlenecks in reality, and the initial location for all agents can increase or decrease the bottlenecks. Finally, we draw some conclusions and point out ways in which this work can be further extended.